Pengembangan Techno Parenting Berbasis Konten Edukasi di Media Sosial untuk Meningkatkan Sinergi antara Orang Tua dan Sekolah - Mudzkia, Agna; Ash-shidiqi, Alfian; Zultiar, Indra (Journal of Comprehensive Science, 2025)
In the digital era, information technology and social media have become an integral part of life, including in children's education. Although technology provides easy access to information, the lack of open communication between parents and teachers becomes an obstacle in creating optimal synergy for child development. Time constraints and parents' busy schedules often hinder their participation in in-person parenting activities, so a more flexible alternative approach is needed. Techno parenting as a solution by integrating technology in parenting, allows parents to access educational materials anytime and anywhere. However, the implementation of techno parenting in Aisyiyah Bustanul Athfal II Kindergarten in Sukabumi City still faces obstacles, such as limited time for teachers to organize materials consistently. Therefore, this study aims to develop a techno parenting model based on educational content on social media to improve synergy between parents and schools. Therefore, the objectives of this research are: 1) integrate technological advances in parenting education, 2) create synergy between parents, schools, and the social environment in building a common perception of children's education. 3) develop a techno parenting model to increase parents' awareness in parenting, and 4) evaluate the effectiveness of the techno parenting model in increasing mindful parenting. The method used is Research and Development (R&D) with the stages of Analysis, Design, Development, Implementation, Evaluation. Where each of these stages is used to produce educational content model products. The results of the evaluation showed that the educational content on social media was effectively used at Aisyiyah Bustanul Athfal 2 Kindergarten in Sukabumi City to improve the synergy between parents and schools.